Supported Ionic Liquid Phase for Biocatalysis: The Current Applications, Synthesis and Prospects - Wolny, Anna; Chrobok, Anna (Current Organic Chemistry, 2023)
In this work, the potential of supported ionic liquids-based biocatalysts was presented. Efforts are underway to identify suitable carrier matrices for biocatalytic reactions, considering the crucial role of surface morphology. Factors such as mechanical and thermal properties, surface area, pore volume, density, and functionalization potential are being carefully considered during selection. The correlation between carrier, enzyme, and il structures highlights the importance of constructing biocatalysts with exceptional catalytic activity. Enzymes immobilized on silp/sillp carriers generally exhibit enhanced activity compared to the native protein. Silp-type carriers improve process efficiency, enable easy separation and recycling of biocatalysts, and prolong the protein's lifespan.
Keywords: SILP/SILLP